Specimen days - Cunningham, Michael 1952- (Farrar, Straus and Giroux, 2005)
In a novel of human progress and social decline, three characters are seen in three different eras: the Industrial Revolution; the 21st century and 150 years into the future as the poet Walt Whitman presides over each episode.
Keywords: New York (N.Y.) -- Fiction; Fiktionale Darstellung